Collaborative Stories of Soul-Nurturing: A Narrative Inquiry into How Counselors and Islamic Education Teachers Foster Spiritual Intelligence - Asmidaryani Asmidaryani (Yayasan Adra Karima Hubbi, 2026)
Background. The development of students’ spiritual intelligence is a fundamental objective of holistic Islamic education because it integrates moral, psychological, and religious dimensions into personal growth. Previous studies have addressed spiritual formation through Guidance and Counseling (GC) or Islamic Education (IE) separately, resulting in fragmented implementation. The lack of systematic collaboration between GC and IE teachers creates a gap in fostering self-awareness, transcendence, meaning-making, and moral behavior. Purpose. This study aims to develop and examine an integrated spiritual development model based on collaboration between GC and IE teachers in enhancing students’ spiritual intelligence. Methods. This study employed an experimental design using a pre-test and post-test control group approach. Sixty students from an Islamic secondary school were divided into experimental and control groups through cluster sampling. The experimental group received the integrated model intervention, while the control group followed conventional instruction. Data were collected using a validated spiritual intelligence questionnaire and classroom observations. Reliability testing showed Cronbach’s alpha above 0.80. Data were analyzed using paired and independent sample t-tests at p < 0.05. Results. Findings show that the experimental group experienced significant improvement in spiritual intelligence compared to the control group. The integrated model enhanced self-awareness, meaning-making, transcendence, and moral behavior. Inferential analysis confirmed significant differences between pre- and post-test scores and between groups. Conclusions. The integrated collaboration model between GC and IE teachers is effective in improving students’ spiritual intelligence. It contributes to holistic Islamic education by bridging counseling and religious instruction and offers practical implications for character education development.